RANDOMIZED COMPARATIVE CLINICAL STUDY TO EVALUATE THE EFFECT OF MAMSYADI KWATHA (ORALLY) ANDTAKRADHARA IN ANIDRA – PRIMARY INSOMNIA (AYUSHDHARA, 2018)
Sleep is a periodic functional state of human being, it is an essential phenomena for maintenance and restoration. That is why Ayurveda stresses on sleep and described as Trayopasthambia. Anidra vis-à-vis Primary insomnia is one of the important diseases pertaining to the Vata disorder affects the people of all age groups. It is particularly relevant to psychiatric illness and frequently part of diagnostic criteria for specific disorder. All the cases with the clinical symptoms of Anidra are selected for the study. In the proposed study, Mamsyadi kwatha which is helpful in producing sleep that is Nidra janak is to be given internally and Takra is to be used for external Dhara which is supposed to be non-invasive process, very simple in administration which can be done for 30 minutes is selected. Based on the earlier studies Jatamamsi, Ashwagandha, Khurasani Yavani are the ingredients of Mamsyadi Kwatha and are well known sleep producing drugs with anti- anxiety and anti-stress qualities. In Dharas, Takradhara is specific procedure for sleep disorders. The constant flow of liquid is continuously poured over the forehead which relaxes the mind, calm and tranquilizes the patients. Assessment is done on the basis of subjective parameter like Jrumbha, Tandra, Angamardia, Shirashool, Manodourbalya, Smritidourbalya, Indriyakarmaheenta, Kantikshya and objective parameter like Athens insomnia scale.The study revealed a noteworthy efficacy of the trial drug in relieving almost all the clinical features within the study duration of 30 days, establishing the versatile action of the drug.